Strategi Pemasaran Rumah Sakit Swasta Non-BPJS Untuk Meningkatkan Pendapatan dan Daya Saing di Industri Layanan Kesehatan - Mursal Salim; Sri Mulyeni (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the marketing strategies implemented by non-BPJS private hospitals in increasing revenue and competitiveness amidst the dominance of BPJS services in Indonesia. Private hospitals face challenges in attracting patients due to the perception of high service costs and limited public access. However, they have advantages in speed of service, modern facilities, and direct access to specialists. This study uses a literature review method with a content analysis approach to various secondary sources such as scientific journals, industry reports, and policy documents. The results of the study indicate that the implementation of a marketing strategy based on the 7P marketing mix concept (product, price, place, promotion, people, process, physical evidence), digital marketing, and customer relationship management through Customer Relationship Management (CRM) are key to increasing patient attraction and loyalty. Collaboration with private insurance also provides added value through ease of payment and access to premium health services. This study provides recommendations for hospitals in developing adaptive, holistic, and patient satisfaction-oriented marketing strategies.